Implementasi Penanaman Nilai-Nilai Moderasi Beragama di Madrasah Ibtidaiyah Tahasus Maarif Nu Pedan Tahun Ajaran 2024/2025 - Hery Suryoko; Yusuf Rahmadi (Jurnal Dirosah Islamiyah, 2024)
This research aims to analyze (1) the implementation of instilling religious moderation values ​​at MI Tahasus Maarif NU Pedan for the 2024/2025 academic year, (2) obstacles to implementing the instillation of religious moderation values, (3) solutions for overcoming obstacles. This research uses a descriptive qualitative approach. Data collection was carried out using interview, observation and documentation techniques. The subjects of this research were Madrasah Heads and Teachers, research informants were Madrasah Heads, Teachers and Students. Activities in data analysis include four processes, namely data collection, data reduction, data presentation and drawing conclusions. The results of the research show: (1) The implementation of instilling the values ​​of religious moderation at MI Tahasus Maarif NU Pedan is carried out by providing understanding to students in the form of materials that related to the values ​​of religious moderation and by holding programs or activities in the aspect of nationalism, for example routinely holding flag ceremonies every Monday, ceremonies commemorating major holidays, watching historical films, study tours. (2) the obstacles are: Students don't pay attention to the teacher during lessons, the learning atmosphere is less supportive, they talk to themselves when learning, students don't understand the material taught by the teacher, there are still students who don't take part in the activities carried out in the program or value instillation activities. -values ​​of religious moderation, There are still teachers who have difficulty collaborating with learning activities and activity programs in instilling the values ​​of religious moderation. (3) Solution: Collaborating themes of religious moderation in subjects, Holding programs or activities to instill the values ​​of religious moderation.